Risk–benefit assessment of foods and its role to inform policy decisions: outcome of an international workshop - Matteu Monteiro, Constanza De; Membré, Jeanne-Marie; Poulsen, Morten; Thomsen, Sofie Theresa; Pires, Sara Monteiro (Frontiers in Nutrition, 2024)
Policy decisions in public health require consideration and evaluation of trade-offs for which transparency and sciencetific-based evidence isare needed. Improvement of decision-support tools is essential to help guide food policy decisions that promote healthy diets and meet the challenges of food systems without compromising food security, food safety, and sovereignty.Risk-benefit assessment of foods (RBA) is an established methodological approach designed to inform policy decisions within the area of nutrition and food safety. Despite methodological developments, translation of RBA findings into policies is still limited. In this context, a stakeholder -workshop held in May 2023 gathered RBArisk-benefit assessment experts and food regulators from Europe to identify the challenges, obstacles and opportunities in using evidence generated through RBAs to inform food policy decisions. A structured process was implemented to collect their views through online surveys, breakout group discussions, and plenary discussions. As a secondary objective, food regulators' views on other approaches for holistic risk assessment fit for food systems analysis were also explored. This paper summarizes the main findings of the workshop and discusses policy implications and future perspectives to improve the area of RBA and its role in food policymaking.